E‐mentoring and its relevance for competency‐based education for students with disabilities: research from the GSAA BreakThru model. Issue 1 (April 2016) - Todd, R.L.; Moon, N.W.; Langston, C.
Abstract : Background: Communication and learning technologies to enable mentoring for students are important topics for online courses and competency‐based education approaches. However, research results have been limited. The Georgia STEM Accessibility Alliance (GSAA) is a research project of the US National Science Foundation's Research in Disabilities Education (RDE) program. It is a collaborative RDE Alliance between the University of Georgia (UGA) and the Georgia Institute of Technology. Launched in 2010, GSAA seeks to enhance achievement of people with disabilities in STEM education and careers. Methods: Core GSAA features are the use of virtual worlds, online, and smartphone technologies to enhance student success through mediated mentoring, collectively referred to as the BreakThru project. Results: Georgia STEM Accessibility Alliance enrolled between 74 and 99 secondary and postsecondary mentees during its 4 years of mentoring activities. Participants involved in these activities reported a higher frequency of usage with communications platforms with which they were already acquainted, including e‐mail, telephone, and SMS text messaging. Positive changes in these students' internal characteristics (self‐advocacy, self‐determination, science and math anxiety, and intention to persist) also were documented. Conclusions: Preliminary results from BreakThru can help inform course designers to maximize mentor/faculty effectiveness with students. Project results indicate both an improvement of student persistence and an improved skill in navigating critical transition points to employment.